Effect of Socioeconomic Status on Patients Supported with Contemporary Left Ventricular Assist Devices. Issue 4 (April 2020) - Clemons, Autumn M.; Flores, Raul J.; Blum, Raia; Wayda, Brian; Brunjes, Danielle L.; Habal, Marlena; Givens, Raymond C.; Truby, Lauren K.; Garan, A. Reshad; Yuzefpolskaya, Melana; Takeda, Koji; Takayama, Hiroo; et al.
Abstract : Continuous-flow left ventricular assist devices (CF-LVADs) are increasingly used in advanced heart failure patients. Recent studies suggest that low socioeconomic status (SES) predicts worst survival after heart transplantation. Both individual-level and neighborhood-level SES (nSES) have been linked to cardiovascular health; however, the impact of SES in CF-LVAD patients remains unknown. We hypothesized that SES is a major determinant of CF-LVAD candidacy and postimplantation outcomes. A retrospective chart review was conducted on 362 patients between February 2009 and May 2016. Neighborhood-level SES was measured using the American Community Survey data and the Agency for Healthcare Research and Quality SES index score. Individual-level SES was self reported. Kaplan–Meier survival analysis and multivariable Cox proportional hazards regression determined survival statistics. Patients in the highest SES tertile were older (58 ± 13 vs. 53 ± 14; p < 0.001), less likely to be black or Hispanic (26% vs. 70%; p < 0.001), more likely to be married (87% vs. 65%; p < 0.001), more likely to have private insurance (50% vs. 39%; p < 0.001), and more likely to have employment (29% vs. 15%; p < 0.001) compared with patients in the lowest tertile. Low nSES was associated with a decreased risk of death (hazard ratio [HR], 0.580; 95% confidence interval [CI], 0.347–0.970; p = 0.038) in comparison to the high nSES. However, after adjusting for baseline clinical morbidities, the relationship was no longer present. When selecting patients for a LVAD, SES should not be thought of as an immutable risk factor. Carefully selected low-SES patients could be safely implanted with CF-LVAD with outcomes comparable to high-SES patients.